Clustering of cardiovascular disease risk factors - Syndemic approach: Is sit a time to shift toward integrated noncommunicable disease clinic? - Kalaiselvi Selvaraj; Sitanshu Sekahr Kar; Gomathi Ramaswamy; K C Premarajan; Ganesh Kumar Saya; Vinodhkumar Kalidoss (Wolters Kluwer Medknow Publications, 2019)
Background: The concurrent occurrence of many noncommunicable disease (NCD) risk factors is common, and it can play a synergistic role in occurrence of NCDs. Objectives: This study aimed to identify the magnitude of clustering of NCD risk factors, patterns of risk factors emerged in clustering, and variations in clustering of risk factors based on socioeconomic factors. Methods: A cross-sectional survey was undertaken in an urban area of Puducherry among 2399 adults during 2014-2015. Sociodemographic and behavioral risk factors were assessed through a validated STEPS survey tool. Individuals with three or more risk factors were classified to have clustering of NCD risk factors. Socioeconomic positions in relation to clustering were identified through Chi-square analysis followed by multiple logistic regression where clustering at family and area was adjusted through multilevel modeling techniques. Results: Of the 2399 adults, 1741 (73%) had clustering of NCD risk factors. Inadequate consumption of fruits and vegetables, high salt intake, and high waist circumference are the three predominant risk factors across all subgroups. Adults belonging to Christian religion (adjusted odds ratio [adjOR]: 2.8, 95% confidence interval [CI]: 1.5-5.2), aged 35 years and over (adjOR: 2.0, 95% CI: 1.4-6.0), and illiterates (adjOR: 1.8, 95% CI: 1.1-5.5) are more likely to have clustered NCD risk factors compared to others. Conclusions: Clustering of NCD risk factors is highly prevalent in this region and mainly driven by dietary practices and obesity measures. There is an urgent need to reorient the health system toward integrated approach with mandated inclusion of nutritionist in NCD health service delivery.